Locating Migrating Media - Elmer, Greg and Davis, Charles. and Marchessault, Janine. and McCullough, John. and Falicov, Tamara L. and Goldsmith, Ben. and Kaye, Janice. and King, Barry. and Moran, Albert. and O'Regan, Tom. (Lexington Books/Fortress Academic, 2010)
Locating Migrating Media details the extent to which media productions, both televisual and cinematic, have sought out new and cheaper shot locations, creative staff, and financing around the world. The book contributes to debates about media globalization, focusing on the local impact of new sites of media production. The book's chapters also question the role that film and television industries and local and regional governments play in broader economic develop and tax incentive schemes.
https://katalog.adlr.link/Record/76-EBC1021881